2019
DOI: 10.1590/1980-5373-mr-2018-0278
|View full text |Cite
|
Sign up to set email alerts
|

Polyhedral Oligomeric Silsesquioxane (POSS) as Reinforcing Agent for Waterborne Polyurethane Coatings on Wood

Abstract: Polyhedral oligomeric silsesquioxane (POSS) was added as a reinforcing agent in waterborne polyurethane (WPU)-based coatings to improve their properties. The morphology, structure, thermal stability as well as mechanical properties of the resulting WPU and WPU/POSS hybrid films were investigated. The good compatibility of POSS in the WPU matrices was demonstrated by transmission electron microscopy. Furthermore, Fourier-transform infrared spectroscopy analysis (FTIR) suggested the successful bonding of POSS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
2
2
0
Order By: Relevance
“…The smaller abrasion-loss value was obtained for this sample compared to the abrasion-loss value of unfilled TPU. Similar findings were reported in recent studies where POSS nanoparticle addition promoted the abrasion resistance of the polyurethane-based composites (Mihelčič et al , 2019; Wei et al , 2019). In those studies, slightly greater abrasion efficiencies were reported compared to the present study, which may be attributed to a better distribution of the POSS nanoparticles using a solution-mixing rather than a melt-mixing technique.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The smaller abrasion-loss value was obtained for this sample compared to the abrasion-loss value of unfilled TPU. Similar findings were reported in recent studies where POSS nanoparticle addition promoted the abrasion resistance of the polyurethane-based composites (Mihelčič et al , 2019; Wei et al , 2019). In those studies, slightly greater abrasion efficiencies were reported compared to the present study, which may be attributed to a better distribution of the POSS nanoparticles using a solution-mixing rather than a melt-mixing technique.…”
Section: Resultssupporting
confidence: 90%
“…Similar findings were postulated in recent studies where POSS nanoparticle addition promoted the abrasion resistance of the polyurethane-based composites (Mihelčič et al, 2019;Wei et al, 2019). In these studies, slightly higher abrasion efficiencies were found relative to our results which may attributed to better distribution of POSS nanoparticles using solution mixing instead of melt-mixing technique.…”
Section: Abrasion Resistancesupporting
confidence: 91%
“…The mechanism of adhesion of coatings is the condensation of free silicone hydroxyl groups in the silicone resin with the silicone hydroxyl groups of the substrate. Because there are more free silicone hydroxyl groups on the surface of wood, we believe that the coatings in this study can also be applied to the surface of wood (Wei et al 2019).…”
Section: Wear Resistancementioning
confidence: 99%
“…The F_POSS formulation presented a higher temperature of maximum degradation as well compared to the industrial one. The value obtained rounded 400 °C, owing to the presence of POSS [ 76 ]. This confirmed the good dispersion and introduction of the filler into the PU system.…”
Section: Resultsmentioning
confidence: 99%